Nitrogen and Hydrogen Adsorption on the Pyrite ${\rm FeS}_2$ (100) Surface: First-Principles Study (Communications in Computational Chemistry, 2018)
Based on density functional theory (DFT), the adsorption of atomic andmolecular hydrogen and nitrogen on pyrite ${\rm FeS}_2 $ (100) surface was studied. Both atomic ${\rm N}$ and ${\rm N}_2$ molecule prefer to adsorb on the top Fe site. The adsorption of atomic ${\rm N}$ onthe surface of ${\rm FeS}_2$ (100) is more stable than ${\rm N}_2.$ Adsorption energy calculation showsthat the adsorption stability weakens with the increase of the ${\rm N}$ atom coverage.Hydrogen adsorption differs quite a lot with that of nitrogen adsorption. It is foundthat atomic ${\rm H}$ could stably adsorbs on ${\rm FeS}_2$ (100) surface at the top Fe site, while ${\rm H}_2$ molecule is quite difficult to adsorb on pyrite ${\rm FeS}_2$ (100) surfaces. The adsorptionstability of atomic hydrogen sharply weakens as the ${\rm H}$ coverage increases.